AI in Digital Business Models Development and Monetization - Maryna LASSOTA; Malgorzata KOCHANOWICZ (Communications of International Proceedings, 2025)
The aim of the article is to present the role that artificial intelligence tools play in contemporary digital business models of the Industry 4.0 economy, with particular emphasis on monetization. The research problem is the question: what role do artificial intelligence tools play in contemporary digital business models of the Industry 4.0 economy, with particular emphasis on monetization. Research niche: existing scientific literature does not sufficiently analyse the impact of AI-based Information and Communication Technologies tools on digital business models of Economy 4.0. Research methods: As the chosen topic of the article is relatively new and dynamic - the literature overview contains elements of narrative and systematic review. Narrative review has been focused on more liberal selection of sources, and qualitative synthesis of the state of research. It requires critical analysis and comparison of concepts but does not always have a formally defined publication selection procedure. Applied systematic review based on clearly defined search and criteria, defined data extraction and synthesis procedure aimed to provide the most objective and repeatable synthesis of all relevant studies, often with a publication flow table and a description of the search strategy. Applied scoping review – was used to map a broad field of research, identifying key themes and gaps, without a detailed assessment of research quality. Main conslusions lead to the statement that literature needs more content that would focus on influence of AI based technologies on companies’ business models.
Keywords: artificial Intelligence; innovations; 4th industrial revolution; Economy 4.0